2017
DOI: 10.1016/s2213-8587(17)30183-3
|View full text |Cite
|
Sign up to set email alerts
|

Measures of chronic kidney disease and risk of incident peripheral artery disease: a collaborative meta-analysis of individual participant data

Abstract: Background Some evidence suggests that chronic kidney disease is a risk factor for lower-extremity peripheral artery disease. We aimed to quantify the independent and joint associations of two measures of chronic kidney disease (estimated glomerular filtration rate [eGFR] and albuminuria) with the incidence of peripheral artery disease. Methods In this collaborative meta-analysis of international cohorts included in the Chronic Kidney Disease Prognosis Consortium (baseline measurements obtained between 1972 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
82
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(94 citation statements)
references
References 44 publications
(65 reference statements)
6
82
0
1
Order By: Relevance
“…Nonetheless, type of medical therapy (no medication, oral glucose lowering, and insulin use) may be used as a surrogate for diabetes severity [25]. Additionally, there is no information on complications of diabetes, specifically kidney disease with albuminuria, which has been shown to be a strong predictor of PAD [26]. …”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, type of medical therapy (no medication, oral glucose lowering, and insulin use) may be used as a surrogate for diabetes severity [25]. Additionally, there is no information on complications of diabetes, specifically kidney disease with albuminuria, which has been shown to be a strong predictor of PAD [26]. …”
Section: Discussionmentioning
confidence: 99%
“…Among the wide spectrum of CV events, a relevant role is portrayed by peripheral vascular disease (PVD). It has been demonstrated that the presence of mild-to-moderate CKD increases the risk of peripheral artery disease, leg revascularization, leg amputation, and hospitalizations [8]. Either an eGFR reduction below 60 mL/min/1.73 m 2 or slight increases of albuminuria (>30 mg/g) have been associated with a 1.5 to 4 times higher risk of peripheral artery disease (PAD).…”
Section: Introductionmentioning
confidence: 99%
“…6 In addition, an individual-level international meta-analysis demonstrated that the 2 key CKD measures, glomerular filtration rate (GFR) and albuminuria, are strongly associated with subsequent risk for PAD. 7 Interestingly, this study demonstrated that albuminuria was especially strongly related to the risk for leg amputation. 7,8 These previous reports highlight the need to understand PAD and CKD in combination.In this issue of AJKD, Bourrier et al 9 provide further evidence highlighting the importance of PAD in the care of patients with CKD.…”
mentioning
confidence: 66%
“…7 Interestingly, this study demonstrated that albuminuria was especially strongly related to the risk for leg amputation. 7,8 These previous reports highlight the need to understand PAD and CKD in combination.…”
mentioning
confidence: 66%
See 1 more Smart Citation